AN INVESTIGATION INTO METAPHORS USED IN ENGLISH AND VIETNAMESE FASHION MAGAZINES - Hoàng Quỳnh Yến (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This study investigated into the use of metaphor in fashion in English and Vietnamese magazines. 300 metaphorical expressions were collected from many famous fashion magazines in English and Vietnamese. The analysis of metaphor was based on both the traditional view of Galperin and the cognitive view of Lakoff and Johnson. This study mainly investigated into the syntactic and semantic features of metaphorical expressions as well as found out the similarities, differences and the frequencies of occurrence of metaphor in fashion magazine language in both languages. Therefore, with the findings in fashion magazines, we hope to contribute to better teaching and learning English as a foreign language. The students and readers can identify and comprehend metaphor in fashion field.